HYPONYMY FOUND IN KATE CHOPIN’S SELECTED SHORT STORIES - Ambat, Fibrianto; Sama, Gratiana; Separ, Fransiskus M (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2024)
This study aimed at explain the types of hyponymy found in Kate Chopin’s selected short stories. Semantic theory and hyponymy approach was used to answer the problem of study. This study used qualitative method. The data were taken of sentence by Kate Chopin selected short stories. The results of this study indicate that there are fifty three of hyponymy with fifteen superordinate it’s grouped in the types of hyponymy found in short stories by Kate Chopin. The types of hyponymy are taxonomic, functional, and collective: singular, heterogeneous stuffs, and collective: plural. Also fifteen superordinate are male, female, number, color, cloth, appearance, tell, see, time distance, size, occupation, part of body, water, and season.